Profiting from Innovation: Evidence from a survey of Queen's Awards winners - Capponi,G; Criscuolo,P; Martinelli,A; Nuvolari,A (Structural Change and Economic Dynamics, 2019)
Based on a survey of firms that received the Queen’s Award for Innovation, we investigate the use and perceived effectiveness of different appropriability strategies in the context of breakthrough innovations. We find that firms consistently combine formal and informal intellectual property to prevent imitation, and that their strategies can vary over time according to the phase of development of the innovation. Our results are consistent also with the growing body of evidence showing that in several economic contexts informal appropriability mechanisms are more effective than patents.